Health Issues and Utilization Pattern of Healthcare Services and Management During and Post Pandemic 2020–2023 in Singapore - Wasnik, Preeti Hemchandra (Digital Repository of Theses - SSBM Geneva, 2025)
The World Health Organization (WHO) declared the COVID-19 pandemic on March 11, 2020, which triggered a global crisis that profoundly impacted health systems, economies, and social well-being (El Keshky MES et al., 2020; Patel U et al., 2020). Immense strain faced by healthcare systems Worldwide. Singapore emerged as a model for effective pandemic management, resulting in a low case fatality rate, through extensive screening, contact tracing, and quarantine measures (Munblit D et al., 2022; Tan et al., 2020; Wong J et al., 2020). Although research has extensively covered acute COVID-19 symptoms, a significant gap exists in understanding healthcare utilization trends and Post-COVID Conditions (PCC) (Munblit D et al., 2022; Smith P et al., 2022). This study explores the health challenges faced by individuals in Singapore during and after the pandemic, focusing on PCC prevalence, healthcare-seeking behaviors, and key factors influencing healthcare access and utilization. This study used a mixed-methods approach and collected quantitative and qualitative. Data from individuals who tested positive for COVID-19 between January 2020 and December 2023. Findings reveal that 80.3% of respondents had contracted COVID-19, with 32.9% reporting persistent health issues, including respiratory, cardiovascular, and mental health complications. Despite Singapore’s well-regulated healthcare system ensuring accessibility during the pandemic, healthcare utilization remained low, influenced by financial concerns, fear of infection, and logistical barriers. Public healthcare services were the preferred choice (71.7%), though post-pandemic trends indicate a gradual shift toward private healthcare for specialized services. Telehealth adoption remained limited (28.3%), suggesting barriers such as technology access and user familiarity. The results underscore the long-term burden of PCC on Singapore’s healthcare system and highlight the urgent need for targeted policy interventions. Recommendations include expanding Long-COVID clinics, enhancing mental health support, and strengthening chronic disease management programs. Understanding healthcare utilization patterns during and after the pandemic is essential for improving accessibility, affordability, and efficiency in healthcare delivery. These insights will assist policymakers, healthcare providers, and researchers in strengthening Singapore’s healthcare system and improving preparedness for future health crises.